The synthesis and properties of oligodeoxyribonucleotides containing N6-methoxyadenine. - Nishio, H (1992)
Oligodeoxyribonucleotides containing N6-methoxyadenine (M) have been synthesized. The order of stability of duplexes consisting of synthesized oligodeoxyribonucleotides, 5'd(CCTGGTAXCAGGTCC)3'-5'd(GGACCTGNTACCAGG)3' (X = M, A, G. N = A, G, T, C), was M: A (Tm = 52 degrees C) greater than M: T (50 degrees C) greater than M: G (48 degrees C) greater than M: C (46 degrees C) observed by thermal denaturation in a buffer of 0.01 M Na cacodylate, and 0.1 M NaCl at pH 7.0. The Tms are within a range of 6 degrees of difference, which is smaller than those of Tms of the duplexes containing A:N pairs (11 degrees) and G:N pairs (11 degrees). DNA replication study on a template-primer system, 5'd(32p-CAGCTTTCGC)3' 3'd(GTCGAAAGCGMAGTCG)5', showed that TTP and dCTP were incorporated into DNA strands at a site opposite to M by Klenow DNA polymerase, but dATP and dGTP were not.